Games in Acquiring First and Second Language Skills - Leztiyani, Indirawati; Nuryani, Nuryani (UIR PRESS, 2023)
Humans are born with tremendous potential in the ability to think. The development of this thinking is a gradual process, with the most critical period occurring during childhood, often referred to as